Pengembangan Sistem Penggajian Berbasis Client Server - Zulhipni Reno Saputra Elsi; Jimmie; Sri Primaini; Hartini (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
The payroll system is very necessary for every company, because every month the company has to pay its obligations to employees, PT. Bintang Gasing Persada has experienced problems in the payroll process, so a client server-based payroll system is needed. The system developed using the waterfall method which has 4 stages of analysis, design, coding and testing, the system was developed using the MySQL database and using the PHP programming language. This payroll system has functions of save, delete, update, automatic reports so that the use process is because the system is user friendly and the processing of employee salaries is more effective.